Saúde da família: desafios no processo de reorientação do modelo assistencial - Costa, Glauce Dias Da; Cotta, Rosângela Minardi Mitre; Ferreira, Maria De Lurdes Da Silva Marques [UNESP]; Reis, José Roberto; Franceschini, Sylvia Do Carmo Castro (Associação Brasileira de Enfermagem, 2009)
The Family Health Program (PSF) constitutes a strategy for reformulating the health assistance model in Brazil. This study was carried out to ponder over the challenges of this strategy concerning to health practices in the primary care context. After existing for more than twelve years, there appear questionings related to the paper of PSF in the reformulation of the way to think and promote health, and their structures remain permeable to the traditional hegemonic model that corrupts the daily work process. Some changes and reconstruction are necessary in the health practices concerning to care production based on light, relational and integrate technologies that are centered on users' needs. Although the deconstruction/reconstruction process implicates much labor, the advantage in overcoming the challenges faced by PSF rather leads to the transformation of reality and to construction of health practices that are solidary, welcoming, and resolvent.

El Programa de la Salud Familia (PSF) se constituye en una estrategia de reformulación del modelo de salud en Brasil. Este estudio tiene como objetivo reflejar sobre los retos del PSF en lo que se refiere a las prácticas de salud en el contexto de la atención primaria. Después de más de doce años de existencia del PSF surgen cuestionamientos en cuanto a la importancia del PSF en la reformulación en la forma de pensar y hacer salud, siendo que sus estructuras persisten permeables al modelo tradicional hegemónico que pervierte el proceso de trabajo cotidiano. Cambios en las prácticas de salud son necesarios en relación a la producción de la atención, basadas en tecnologías leves, relacionales, integradas, y centradas en las necesidades de los usuarios. El proceso de reconstrucción implica en arduo trabajo, mas la ventaja de la superación de los retos enfrentados por el PSF lleva a la transformación de la realidad y la construcción de prácticas de salud solidarias, acogedoras y consecuentemente más efectivas y de resolución.

O Programa Saúde da Família (PSF) constitui-se em uma estratégia de reformulação do modelo assistencial de saúde no Brasil. Este estudo tem como objetivo refletir sobre os desafios desta estratégia quanto às práticas de saúde no contexto da atenção primária. Foi realizado um estudo bibliográfico, 90 artigos foram selecionados, sendo 50 considerados de maior interesse. Após quatorze anos de existência, surgem questionamentos quanto ao papel do PSF, suas estruturas continuam permeáveis ao modelo hegemônico que corrompe o processo de trabalho cotidiano. Mudanças nas práticas de saúde, especialmente, no que tange a produção de cuidados, são necessárias e este processo de reconstrução implica muito labor. No entanto, possibilita a construção de práticas de saúde mais solidárias, acolhedoras e conseqüentemente mais resolutivas.
Family health: challenges in the reorientation process of the assistance model
Salud de la familia: desafíos en el proceso de reorientación del modelo de atención
Keywords: Family health; Primary health care; Family Health Program; Saúde da família; Atenção primária; Programa Saúde da Família